Financial Planning and Management Strategy in Increasing Profitability - Zuriani Ritonga; Hayanuddin safri; Karimi; Sri Murniyanti; M.Yusuf (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the role of financial planning and management strategies in improving corporate profitability. Using a systematic literature review approach by examining 20 references from national and international scientific journals, this study found that effective financial planning, encompassing budgeting, cash flow management, and financial statement analysis, significantly contributes to profitability improvement. Furthermore, management strategies such as cost efficiency, product diversification, and asset optimization further strengthen organizational financial performance. Findings indicate that the integration of long-term financial planning and adaptive management strategies produces sustainable competitive advantages. This research provides theoretical and practical contributions for financial managers and policy makers in designing strategies oriented towards optimal growth and profitability.